Upaya KUA Kecamatan Jombang Dalam Mencegah Pernikahan Dini Perspektif Maslahah Mursalah Tahun 2022-2023 - Ayatulloh Masyhudi; Muhammad Muhammad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Marriage is a powerful vow, or misaqan galizan, and doing it to follow Allah's will is worth worship. According to Law Number 16 of 2019, which later revised Law Number 1 of 1974, the minimum age for marriage is 19 years. Despite this, society still makes exceptions to this rule, which is where the term